Effects of Salinity Changes on the Growth of Dunaliella salina and Its Isozyme Activities of Glycerol-3-phosphate Dehydrogenase - Chen, H.; Jiang, J.; Wu, G.
Dunaliella salina could survive in media containing a wide range of NaCl concentrations ranging from about 0.05 M to saturation (around 5.5 M). Glycerol is an important osmolyte when Dunaliella survive in various salt environments, and G3pdh is a key enzyme in glycerol metabolism. The osmotic response of D. salina was investigated by studying its cell growth, glycerol content change, and isozyme activity of glycerol-3-phosphate dehydrogenase (G3pdh)in different salinities. Results showed that 2.0 M NaCl was the optimal salinity for the growth of D. salina, in which condition the highest glycerol content of 64.02 ( 3.21 (mean ( SD)ìg/mL was detected. D. salina could rapidly increase or decrease glycerol contents to adapt to hypoosmotic or hyperosmotic environments. The glycerol content declined 52.05
Keywords: DUNALIELLA SALINA; OSMOTIC; GLYCEROL; SALINITY; ISOZYME; GLYCEROL-3-PHOSPHATE DEHYDROGENASE